2005
DOI: 10.1002/ls.3010170202
|View full text |Cite
|
Sign up to set email alerts
|

Recent achievements in the synthesis and application of inorganic nanoparticles as lubricant components

Abstract: Recent advances made in the chemistry and technology of nano‐metric inorganic particles allow the synthesis of various metal oxides, chalcogenides, phosphates, and so on. Surface modification of nanoparticles in some cases allows the formation of stable dispersions in liquid hydrocarbons. The state of the art in the field of inorganic nanoparticle synthesis and their application in tribology are discussed in this paper. Special attention is paid to the synthesis of surface‐capped and bare molybdenum sulphide n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Reviews of the use of nanoparticles in lubricants can be found in [209][210][211]. Many different types of material have been examined as colloidal additives to reduce both friction and wear, but the most common are metals, metallic oxides, borates and phosphates, fullerenes, inorganic fullerenes, boron oxide and nitride and recently graphene.…”
Section: Nanoparticle Additive Research; 1990 To Presentmentioning
confidence: 99%
“…Reviews of the use of nanoparticles in lubricants can be found in [209][210][211]. Many different types of material have been examined as colloidal additives to reduce both friction and wear, but the most common are metals, metallic oxides, borates and phosphates, fullerenes, inorganic fullerenes, boron oxide and nitride and recently graphene.…”
Section: Nanoparticle Additive Research; 1990 To Presentmentioning
confidence: 99%
“…The binding energy of iron (Fe2p) locates at 707.1 and 711.2 eV, respectively, corresponded to Fe 3+ (oxide), i.e. to Fe2O3 [30,32,[40][41][42]44]. Fe2p spectra showed a presence of Fe 2+ and Fe 3+ .…”
Section: Tribological Mechanisms Of Tio2 Nanoparticlesmentioning
confidence: 99%
“…Nanoparticles have efficient lubrication features in addition to their satisfactory cooling performance. Therefore, the tool flank wear is much reduced and this brings out many benefits: (1) increasing hob life, (2) reducing the gear profile error, (3) improvement of gear surface smoothness and (4) reducing the friction force.…”
Section: Evaluation Of Hob Wearmentioning
confidence: 99%
“…In recent times, nanofluid, a fluid containing nanoparticle such as Al 2 O 3 , WS 2 , MoS 2 , have been effectively used by their cooling lubrication for the gear transmission [1]. Compared to the general industrial lubricants, the nanolubricant can not only reduce the coefficient of friction but also increase heat transfer [2]. In the machining field [3], the recent study of nanofluid exhibits the promising results as reducing cutting temperature, improving surface finish, and decreasing tool wear.…”
mentioning
confidence: 99%